Development of Safety Star Grading Program: A Star Rating System for Express Bus Operator in Malaysia - Ahmad, M.S.; Ameer Batcha, W.; Othman, I.; Ariffin, A.H. (Journal of the Society of Automotive Engineers Malaysia, 2021)
In 2007, the Malaysian Institute of Road Safety Research (MIROS) with engagement from numerous stakeholders has come out with a Safety, Health and Environment Code of Practice (SHE COP). The main reason for the existence of this SHE COP is because of a drastic increase in the number of crashes within the five years involving commercial vehicles especially express buses. Subsequently, in 2010, SHE COP has been gazetted as Industrial Code of Practice for Transportation Sector (ICOP 2010) under the Occupational Safety and Health Act 1994 (OSHA 1994). This ICOP 2010 can be used as guidelines to improve safety management for fleet operators. However, it has limitations to disseminate information to the public on the level of safe operation by the operators for them to make a good decision. Through some focus group discussions, a review of ICOP 2010, and a pilot test, MIROS has developed a star rating system named as Safety Star Grading Program (SSG) to provide information to the public on the level of safety management and service performance of the express bus operators. This SSG rating criteria consist of 4 elements which are safety, health, service performance, and comfort. Under the safety element, there are six sub-elements which are policy, organization, planning and implementation, evaluation, and action. Overall, this SSG was developed by referring to the basic concept of a safety management system to provide public transportation users with information to make a better decision on choosing the safest operator.